Secondary battery and electric device
By using sustained release polymer in the positive electrode sheet of the secondary battery, it dissolves in the electrolyte during the cycle, the problem of low diffusion efficiency of active ions in the prior art is solved, and the cycle stability and capacity of the battery are improved Retention rate.
Patent Information
- Application Number
- CN202310799145.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the existing secondary batteries, under high temperature or high rate charging and discharge conditions, the diffusion efficiency of active ions is low, resulting in a decrease in circulation stability and capacity, and the binder cannot dissolve in the electrolyte, hindering the embedding/embedding of ions.
The introduction of sustained release polymer into the positive electrode sheet of the secondary battery can be dissolved in the electrolyte during the cycle, reducing polarization resistance, increasing porosity, improving the diffusion efficiency of lithium ions, and passing the appropriate polymer and adhesive The proportion of the preparation agent is combined to optimize the circulation performance of the battery.
It significantly improves the cycle life of the secondary battery and the cycle performance at high magnifications, ensuring the stability and capacity retention of the battery under high temperature conditions.
Smart Images

Figure CN119230911A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's performance requirements for secondary batteries have become increasingly higher.
[0003] As the requirements for the battery life of electrical devices continue to increase, there is an urgent need to further improve the cycle stability of secondary batteries. Summary of the invention
[0004] In view of the problems existing in the background technology, the present application provides a secondary battery, aiming to improve the cycle stability of the secondary battery.
[0005] A first aspect of the present application provides a secondary battery, comprising a positive electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode film layer containing a slow-release polymer, and the slow-release polymer can be dissolved in the electrolyte during the cycle of the secondary battery.
[0006] During the cycle of the secondary battery, the slow-release polymer will be released from the positive electrode and dissolved in the electrolyte. On the one hand, the polarization resistance of the positive electrode is reduced, and the metal ions (such as lithium ions) in the active material can be completely released, thereby improving the cycle life of the secondary battery. On the other hand, the release of the slow-release polymer will increase the porosity of the positive electrode, improve the diffusion efficiency of metal ions (such as lithium ions) and the cycle performance of the secondary battery at high rates.
[0007] In any embodiment, at 20°C to 25°C, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no greater than 2J 1 / 2 / cm 3 / 2 .
[0008] At 20℃~25℃, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no more than 2J 1 / 2 / cm 3 / 2 The molecular chain of the slow-release polymer is easy to diffuse in the solvent, that is, the slow-release polymer has good solubility in the solvent of the electrolyte. The slow-release polymer released from the electrode can be dissolved in the solvent of the electrolyte, reducing the negative impact on the subsequent cycles of the battery.
[0009] In any embodiment, the weight average molecular weight of the sustained-release polymer is 25,000-200,000, and can be optionally 60,000-150,000.
[0010] The weight average molecular weight of the slow-release polymer is 25,000-200,000, which can not only make the slow-release polymer have sufficient adhesion to facilitate the molding of the pole piece, but also make the polymer easy to slow-release and dissolve in the solvent of the electrolyte, thereby improving the cycle stability of the battery. The slow-release polymer with a weight average molecular weight of 60,000-150,000 can further optimize the cycle stability of the battery.
[0011] In any embodiment, based on the total mass of the positive electrode film layer, the mass percentage of the slow-release polymer is not higher than 4%, and can be optionally 0.5%-2%.
[0012] If the mass percentage of the slow-release polymer is too high, it will affect the bonding performance of the pole piece, and then have a negative effect on the cycle stability of the battery. If the mass percentage of the slow-release polymer is too low, the slow-release polymer cannot effectively play its role, which is not conducive to improving the battery cycle performance. The slow-release polymer with a mass percentage of 0.5%-2% can effectively play a slow-release role without affecting the bonding performance of the pole piece, and comprehensively improve the cycle performance of the battery.
[0013] In any embodiment, the sustained-release polymer includes at least one of an ester polymer, an ether polymer, a polymer containing a cyano group, or a polymer containing a benzene ring.
[0014] The above polymer not only has good solubility in electrolyte solvents, but also has high adhesion, mechanical strength and chemical stability. It can play the role of a binder when the pole piece is formed, and can play a sustained release role when the battery is in use, thereby optimizing the cycle stability of the battery.
[0015] In any embodiment, the sustained-release polymer comprises at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile or polystyrene.
[0016] In any embodiment, the sustained-release polymer comprises an ester polymer, and the electrolyte comprises an ester solvent.
[0017] Both ester polymers and ester solvents contain ether bonds, have similar solubility parameters, and have good compatibility, which is beneficial to improving battery cycle performance.
[0018] In any embodiment, the sustained-release polymer includes an ether polymer, and the electrolyte includes an ether solvent.
[0019] Both ether polymers and ether solvents contain ether bonds, have similar solubility parameters, and have good compatibility, which is beneficial to improving battery cycle performance.
[0020] In any embodiment, the positive electrode film layer further includes a binder, and the mass ratio of the slow-release polymer to the binder is 1:2.5-1:0.5, and can be optionally 1:2-1:0.8.
[0021] Through the effective ratio matching between the slow-release polymer and the binder, the adhesion and slow-release performance of the electrode can be taken into account at the same time, and the cycle performance of the battery can be comprehensively improved.
[0022] In any embodiment, the viscosity of the electrolyte is 0.75 mPa·s-1.50 mPa·s, and can be optionally 0.96 mPa·s-1.15 mPa·s.
[0023] The viscosity of the electrolyte is within an appropriate range so that the electrolyte maintains good ionic conductivity, further reduces electrode polarization, and improves the cycle performance of the battery, especially the cycle stability at high rates.
[0024] In any embodiment, the secondary battery includes at least one of a lithium secondary battery, a sodium secondary battery, a magnesium secondary battery, and a potassium secondary battery.
[0025] A second aspect of the present application provides an electrical device, comprising the secondary battery of the first aspect.
[0026] The third aspect of the present application provides use of a polymer, wherein the polymer is used as a slow-release polymer in the secondary battery of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0028] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0029] Figure 3 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0030] Reference numerals:
[0031] 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0032] Below, the secondary battery and the embodiment of the electric device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0033] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0034] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0035] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0036] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0037] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0038] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0039] In the prior art, in order to ensure the battery life, the binder in the pole piece usually adopts a solvent-resistant polymer, that is, the binder in the pole piece cannot be dissolved in the solvent of the electrolyte, such as a polymer with poor compatibility with the solvent of the electrolyte, a cross-linked polymer, etc. A cross-linked polymer refers to a network polymer or polymer formed by chemical bonds between polymer chains. The cross-linking reaction can occur during the polymerization reaction, or a chemical reaction can be used to cross-link the linear polymer after the polymer is formed. The cross-linked polymer has the characteristics of being insoluble and infusible. When the degree of cross-linking is low, the cross-linked polymer can swell in the solvent. As the degree of cross-linking increases, the swelling degree of the cross-linked polymer decreases, and the solvent resistance is enhanced.
[0040] Although solvent-resistant polymers help to maintain the positive electrode active material on the electrode for a long time, they will also hinder the diffusion of active ions (such as lithium ions) on the positive electrode electrode, which is not conducive to the deintercalation of active ions in the positive electrode active material. Especially under high temperature or high-rate charging and discharging conditions, the polarization internal resistance increases significantly with the increase of current density, and the active ions cannot be quickly embedded / embedded, resulting in a decrease in the reversible capacity of the battery and a decrease in the cycle stability.
[0041] [Secondary battery]
[0042] Based on this, the present application provides a secondary battery, comprising a positive electrode plate and an electrolyte, wherein the positive electrode plate comprises a positive electrode film layer containing a slow-release polymer, and the slow-release polymer can be dissolved in the electrolyte during the cycle of the secondary battery.
[0043] During the charge and discharge cycle of the secondary battery, the electrolyte will repeatedly infiltrate the positive electrode sheet and repeatedly squeeze out of the positive electrode sheet as the battery expands and contracts. Under the infiltration of the electrolyte, the slow-release polymer in the positive electrode sheet will gradually be released from the positive electrode sheet and dissolved in the electrolyte. On the one hand, the polarization resistance of the positive electrode sheet is reduced, and the active ions (such as lithium ions) in the active material can be fully released, thereby improving the cycle life of the secondary battery; on the other hand, the release of the slow-release polymer will increase the porosity of the positive electrode sheet, improve the diffusion efficiency of active ions (such as lithium ions) and the cycle performance of the secondary battery at high rates.
[0044] In some embodiments, at 20°C to 25°C, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no greater than 2J 1 / 2 / cm 3 / 2 .
[0045] The solubility parameter δ is often used to characterize the miscibility between different substances. The solubility parameter δ can be expressed as follows
[0046]
[0047] Where ΔE is the cohesive energy of the substance, in J; V is the molar volume of the substance, in cm 3 According to the principles of thermodynamics, the greater the difference in solubility parameters δ between two substances, the greater the change in system enthalpy after the two substances are mixed, and the probability of the system reaching thermodynamic compatibility decreases accordingly. The smaller the absolute value of the difference in solubility parameters between different substances, the better it is to improve the solubility between substances.
[0048] The solubility parameter can be measured by any method in the art. As an example, the solubility parameter can be measured by the intrinsic viscosity method. Prepare solvents with different solubility parameter values, measure the intrinsic viscosity of the sustained-release polymer in these solvents respectively, plot the intrinsic viscosity against the solubility parameter of the corresponding solvent, and take the solubility parameter value corresponding to the maximum intrinsic viscosity as the solubility parameter value of the polymer. The intrinsic viscosity refers to the limit value of the reduced viscosity or the reduced logarithmic viscosity of an infinitely diluted polymer solution. The intrinsic viscosity can be measured by any known method in the art. As an example, the intrinsic viscosity can be measured by the dilution method specified in the national standard GB / T12005.1-1989.
[0049] It can be understood that the sustained-release polymer may include only one polymer or multiple polymers. The solvent of the electrolyte may include only one solvent compound or multiple solvent compounds.
[0050] At 20℃~25℃, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no more than 2J 1 / 2 / cm3 / 2 The molecular chain of the slow-release polymer is easy to diffuse in the solvent, that is, the slow-release polymer has good solubility in the solvent of the electrolyte. The slow-release polymer released from the electrode can be dissolved in the solvent of the electrolyte, reducing the negative impact on the subsequent cycles of the battery.
[0051] In some embodiments, the sustained-release polymer includes an ester polymer. An ester polymer refers to a polymer containing an ester functional group in a structural unit, and as an example, includes but is not limited to polymethyl methacrylate, polyethyl methacrylate, polypropyl methacrylate, polyn-butyl methacrylate, polyt-butyl methacrylate, polyn-hexyl methacrylate, polylauryl methacrylate, polyisobornyl methacrylate, polyoctadecyl methacrylate, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, and a block copolymer of polymethyl methacrylate-propylene sulfite.
[0052] In some embodiments, the sustained-release polymer includes an ether polymer, which refers to a polymer containing an ether bond in a structural unit, and includes, but is not limited to, polyethylene oxide and polypropylene oxide.
[0053] In some embodiments, the electrolyte includes at least one of an ester solvent and an ether solvent. An ester solvent refers to an ester compound that can be used as a solvent. An ether solvent refers to an ether compound that can be used as a solvent.
[0054] In some embodiments, the slow-release polymer includes an ester polymer; the electrolyte includes an ester solvent. Both the ester polymer and the ester solvent contain ester functional groups, and the solubility parameters of the two are similar, and they have good compatibility. In some embodiments, the slow-release polymer includes polymethyl methacrylate, and the electrolyte includes an ester solvent. In some embodiments, the slow-release polymer includes a block copolymer of polymethyl methacrylate-propylene sulfite, and the electrolyte includes an ester solvent. In some embodiments, the ester solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, and 1,4-butyrolactone.
[0055] In some embodiments, the sustained-release polymer includes an ether polymer; the electrolyte includes an ether solvent. Both the ether polymer and the ether solvent contain ether bonds, and the solubility parameters of the two are similar, and they have good compatibility. In some embodiments, the sustained-release polymer includes polyethylene oxide, and the electrolyte includes an ether solvent. In some embodiments, the ether solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol formic acid ethyl ether, ethylene glycol dibutyl ether, 1,3-dioxolane, 1,4-dioxane, tetrahydrofuran, and methyltetrahydrofuran.
[0056] In some embodiments, the sustained-release polymer includes at least one of an ester polymer, an ether polymer, a polymer containing a cyano group, and a polymer containing a benzene ring.
[0057] The above polymer not only has good solubility in electrolyte solvents, but also has high adhesion, mechanical strength and chemical stability. It can play the role of a binder when the pole piece is formed, and can play a sustained release role when the battery is in use, thereby optimizing the cycle stability of the battery.
[0058] In some embodiments, the sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile, and polystyrene.
[0059] In some embodiments, the weight average molecular weight of the sustained-release polymer is 25,000-200,000, and can be optionally 60,000-150,000.
[0060] In this article, the term "weight average molecular weight" refers to the statistical average of the mass fractions of each fraction in the polymer. The polymer can be characterized by the sum of the weight fractions of molecules of different molecular weights multiplied by their corresponding molecular weights.
[0061] In the present application, the weight average molecular weight of the polymer can be tested by methods known in the art, such as gel chromatography, such as Waters 2695Isocratic HPLC gel chromatograph (differential refractive index detector 2141). In some embodiments, the test method is to use a polystyrene solution sample with a mass fraction of 3.0% as a reference, and select a matching chromatographic column (oily: Styragel HT5DMF7.8*300mm+Styragel HT4). Use purified N-methylpyrrolidone (NMP) solvent to prepare a 3.0% polymer glue, and let the prepared solution stand for one day for use. During the test, first use a syringe to draw tetrahydrofuran, rinse, and repeat several times. Then draw 5 ml of the experimental solution, remove the air in the syringe, and wipe the needle tip dry. Finally, slowly inject the sample solution into the injection port. After the reading is stable, obtain the data and read the weight average molecular weight.
[0062] In some embodiments, the weight average molecular weight of the sustained-release polymer can be selected as 25,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000 or 200,000.
[0063] The weight average molecular weight of the slow-release polymer is 25,000-200,000, which can not only make the slow-release polymer have sufficient adhesion to facilitate the molding of the pole piece, but also make the polymer easy to slow-release and dissolve in the solvent of the electrolyte, thereby improving the cycle stability of the battery. The slow-release polymer with a weight average molecular weight of 60,000-150,000 can further optimize the cycle stability of the battery.
[0064] In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the slow-release polymer is no more than 4%, and can be optionally 0.5%-2%.
[0065] In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the sustained-release polymer may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, or 4%.
[0066] If the mass content of the slow-release polymer is too high, it will affect the bonding performance of the pole piece, and then have a negative effect on the cycle stability of the battery. If the mass content of the slow-release polymer is too low, the slow-release polymer cannot effectively play its role, which is not conducive to improving the battery cycle performance. The slow-release polymer with a mass content of 0.5%-2% can effectively play a slow-release role without affecting the bonding performance of the pole piece, and comprehensively improve the cycle performance of the battery.
[0067] In some embodiments, the positive electrode film layer further includes a binder, and the mass ratio of the slow-release polymer to the binder is 1:2.5-1:0.5, and can be optionally 1:2-1:0.8.
[0068] In some embodiments, the positive electrode film layer further includes a binder, and the mass ratio of the slow-release polymer to the binder can be 1:2.5, 1:2, 1:1.5, 1:1, 1:0.8, or 1:0.5.
[0069] Through the effective ratio matching between the slow-release polymer and the binder, the adhesion and slow-release performance of the electrode can be taken into account at the same time, and the cycle performance of the battery can be comprehensively improved.
[0070] In some embodiments, the viscosity of the electrolyte is 0.75 mPa·s-1.50 mPa·s, and can be optionally 0.96 mPa·s-1.15 mPa·s.
[0071] In some embodiments, the viscosity of the electrolyte may be 0.75 mPa·s, 0.80 mPa·s, 0.85 mPa·s, 0.90 mPa·s, 0.96 mPa·s, 1 mPa·s, 1.15 mPa·s, 1.25 mPa·s, 1.29 mPa·s, or 1.50 mPa·s.
[0072] The viscosity of the electrolyte can be measured by any known method in the art. As an example, the viscosity of the electrolyte can be measured using a rotational viscometer.
[0073] The viscosity of the electrolyte is within an appropriate range so that the electrolyte maintains good ionic conductivity, further reduces electrode polarization, and improves the cycle performance of the battery, especially the cycle stability at high rates.
[0074] In some embodiments, the secondary battery includes at least one of a lithium secondary battery, a sodium secondary battery, a magnesium secondary battery, and a potassium secondary battery.
[0075] In some embodiments, the cathode film layer includes a cathode active material.
[0076] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0077] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0078] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material of a lithium secondary battery may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0079] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0080] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0081] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and the slow-release polymer, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0082] [Negative electrode]
[0083] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0084] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0085] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0086] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0087] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0088] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0089] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0090] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0091] [Electrolytes]
[0092] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0093] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0094] In some embodiments, the electrolyte salt of the lithium secondary battery can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0095] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0096] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0097] [Isolation film]
[0098] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0099] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0100] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0101] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0102] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0103] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0104] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0105] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0106] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0107] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0108] Figure 3 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0109] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0110] The present application also provides a use of a polymer, wherein the polymer is used as a slow-release polymer in a secondary battery of any embodiment.
[0111] Example
[0112] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0113] 1. Preparation method
[0114] Example 1
[0115] 1) Preparation of positive electrode
[0116] Weigh the positive electrode active material lithium iron phosphate (theoretical gram capacity is 139 mAh / g), the conductive agent acetylene black, the binder PVDF, and the slow-release polymer polymethyl methacrylate (PMMA) in a mass ratio of 96:2:1:1. Add the solvent N-methylpyrrolidone, stir and mix thoroughly to obtain a stable positive electrode slurry. Apply the above positive electrode slurry containing the slow-release polymer on both surfaces of the positive electrode current collector aluminum foil, where the coating weight of the positive electrode slurry is 0.224g / 1540.25mm 2 (measured in terms of solid content), and then dried and cold pressed to obtain the positive electrode sheet.
[0117] 2) Preparation of negative electrode sheet
[0118] The negative electrode active material artificial graphite (gram capacity of 340 mAh / g), the conductive agent acetylene black, styrene butadiene rubber (SBR), and carboxymethyl cellulose CMC were mixed in a weight ratio of 95:1.5:3.1:0.4, and the solvent deionized water was added, and the mixture was stirred and mixed to obtain a negative electrode slurry, which was then coated on both surfaces of the negative electrode current collector copper foil, wherein the coating weight of the negative electrode slurry was 0.108 g / 1540.25 mm 2 (based on solid content), and after drying and cold pressing, the negative electrode sheet is obtained.
[0119] 3) Preparation of electrolyte
[0120] In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), polycarbonate (PC), and dimethyl carbonate (DMC) were mixed at a mass ratio of EC:PC:DMC=3:3:3, and then LiPF 6 , vinylene carbonate (VC), vinyl sulfate (DTD), 1,3-propane sultone are added to a mixed organic solvent and stirred to obtain an electrolyte, wherein LiPF 6 The concentration in the electrolyte is 1 mol / L, and the mass percentages of VC, DTD, and 1,3-propane sultone are 3%, 1%, and 1%, respectively.
[0121] 4) Isolation film
[0122] A polyethylene film (PE membrane) is used as the isolation membrane.
[0123] 5) Preparation of batteries
[0124] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with a prepared electrolyte, and packaged for formation to obtain a lithium-ion battery.
[0125] The preparation methods in Examples 2-5 are basically the same as those in Example 1, except that the type of the sustained-release polymer is adjusted. Specifically, in Example 2, the sustained-release polymer is a mixture of polymethyl methacrylate and polyethylene oxide (PEO), and the mass ratio of the two is 1:0.55; in Example 3, the sustained-release polymer is a mixture of polymethyl methacrylate and polystyrene (PS), and the mass ratio of the two is 1:0.75; in Example 4, the sustained-release polymer is polystyrene; in Example 5, the sustained-release polymer is a mixture of polymethyl methacrylate and polyacrylonitrile, and the mass ratio of the two is 1:0.8.
[0126] The preparation methods of Examples 6-9 are basically the same as those of Example 1, except that the mass percentage of the sustained-release polymer is adjusted, and the mass percentage of the positive electrode active material is adjusted accordingly. In Example 6, the positive electrode active material lithium iron phosphate (theoretical gram capacity is 139 mAh / g), the conductive agent acetylene black, the binder PVDF, and the sustained-release polymer polymethyl methacrylate (PMMA) are mixed according to 96.5:2:1:0.5; in Example 7, the positive electrode active material lithium iron phosphate (theoretical gram capacity is 139 mAh / g), the conductive agent acetylene black, the binder PVDF, and the sustained-release polymer In Example 8, the positive electrode active material lithium iron phosphate (theoretical gram capacity is 139 mAh / g), the conductive agent acetylene black, the binder PVDF, and the slow-release polymer polymethyl methacrylate (PMMA) are mixed according to 95:2:1:2; in Example 9, the positive electrode active material lithium iron phosphate (theoretical gram capacity is 139 mAh / g), the conductive agent acetylene black, the binder PVDF, and the slow-release polymer polymethyl methacrylate (PMMA) are mixed according to 93:2:1:4.
[0127] The preparation methods of Examples 10-13 are basically the same as that of Example 1, except that the weight average molecular weight of the sustained-release polymer is adjusted, as shown in Table 1.
[0128] The preparation methods in Examples 14-17 are basically the same as those in Example 1, except that the total mass of the sustained-release polymer and the binder PVDF is kept constant and the mass ratio of the two is adjusted.
[0129] In Example 18, the slow-release polymer is PEO, and the electrolyte preparation method is as follows:
[0130] Ether electrolyte: In an argon atmosphere glove box with a water content of <10ppm, including lithium salt, solvent and diluent, the lithium salt includes LiPF 6 The solvent includes dimethyl ether (DME), the diluent includes hydrofluoroether (HFE), the volume ratio of the solvent to the diluent is 1:2, and the mixture is uniform. 6 , vinylene carbonate (VC), vinyl sulfate (DTD), 1,3-propane sultone are added to a mixed organic solvent and stirred to obtain an electrolyte, wherein LiPF 6 The concentration in the electrolyte is 1 mol / L, and the mass percentages of VC, DTD, and 1,3-propane sultone are 3%, 1%, and 1%, respectively.
[0131] Other preparation methods are the same as in Example 1.
[0132] In Comparative Example 1, no sustained-release polymer was added, and the rest was the same as in Example 1.
[0133] In Comparative Example 2, no sustained-release polymer was added, and the rest was the same as in Example 18.
[0134] 2. Test Method
[0135] 1) High temperature and high rate cycle performance
[0136] At 60°C, the lithium-ion battery is first charged at a constant current of 1C (i.e., the current value that completely discharges the theoretical capacity within 1 hour) to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C. After standing for 5 minutes, the lithium-ion battery is discharged at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The lithium-ion battery is subjected to multiple cycle charge and discharge tests according to the above method, and the discharge capacity of the 500th cycle is detected.
[0137] The capacity retention rate of the lithium ion battery after 500 cycles at 60° C. = (discharge capacity at the 500th cycle / discharge capacity at the first cycle)×100%.
[0138] 2) Viscosity test
[0139] Use a rotating viscometer to measure the viscosity of the electrolyte. Select a suitable rotor, fix the viscometer rotor, place the electrolyte before the cycle and the electrolyte after 500 cycles under the viscometer rotor, and the electrolyte just submerges the scale line of the rotor. Instrument model: Shanghai Fangrui NDJ-5S, rotor is 62#, the speed is 30 rpm, and the measurable viscosity range is 0-1000mPa·s; rotor is 63#, the speed is 30 rpm, and the measurable viscosity range is 0-2000mPa·s), test temperature: 25℃, test time is 5 minutes, and read the data after the display is stable.
[0140] 3) Solubility parameter test
[0141] The solubility parameter is measured by the intrinsic viscosity method. Solvents with different solubility parameter values are prepared, and the intrinsic viscosity of the sustained-release polymer in these solvents is measured respectively. The intrinsic viscosity and the solubility parameter of the corresponding solvent are plotted, and the solubility parameter value corresponding to the maximum intrinsic viscosity is taken as the solubility parameter value of the polymer.
[0142] 4) Battery discharge capacity test
[0143] The discharge capacity test process is as follows: at 25°C, the prepared battery is charged to 3.75V at a constant current of 1C, then charged at a constant voltage of 3.75V until the current drops to 0.05C, and then discharged to 1.5V at a constant current of 1C to obtain the battery discharge capacity (Cd1).
[0144] III. Analysis of test results of various embodiments and comparative examples
[0145] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1-3 below.
[0146] Table 1
[0147]
[0148] Table 2
[0149]
[0150] Table 3
[0151]
[0152] From the comparison between Examples 1-18 and Comparative Example 1, it can be seen that the positive electrode film layer includes a slow-release polymer that can be dissolved in the electrolyte, which is beneficial to improving the cycle stability of the battery.
[0153] The absolute value of the difference between the solubility parameter of the slow-release polymer in Examples 1-18 and the electrolyte solvent at 20°C to 25°C is less than 2J. 1 / 2 / cm 3 / 2 The slow-release polymer has good compatibility with the electrolyte, which is beneficial to improving the cycle stability of the battery.
[0154] It can be seen from Examples 1-18 that polymethyl methacrylate, polyethylene oxide, polyacrylonitrile and polystyrene can all be used as sustained-release polymers to improve the cycle stability of the battery.
[0155] As can be seen from Examples 6-9, when the mass percentage of the slow-release polymer is not higher than 4% based on the total mass of the positive electrode film layer, the cycle capacity retention rate of the battery is improved. When the mass percentage of the slow-release polymer is 0.5%-2% based on the total mass of the positive electrode film layer, the cycle capacity retention rate of the battery is further improved.
[0156] It can be seen from Examples 10-13 that when the weight average molecular weight of the slow-release polymer is 25,000-200,000, the cycle capacity retention rate of the battery is improved. When the weight average molecular weight of the slow-release polymer is 60,000-150,000, the cycle capacity retention rate of the battery is further improved.
[0157] It can be seen from Examples 14-17 that when the mass ratio of the slow-release polymer to the binder is 1:2.5-1:0.5, the cycle capacity retention rate of the battery is improved. When the mass ratio of the slow-release polymer to the binder is 1:2-1:1, the cycle capacity retention rate of the battery is further improved.
[0158] As can be seen from Examples 1-18, along with the cycle reaction of the battery, the slow-release polymer gradually dissolves in the electrolyte, causing the viscosity of the electrolyte to increase. However, the viscosity of the electrolyte is controlled between 0.75mPa·s-1.50mPa·s to reduce the deterioration of the electrochemical performance of the secondary battery caused by the increase in the viscosity of the electrolyte. Controlling the viscosity of the electrolyte between 0.96mPa·s-1.15mPa·s can further improve the high-temperature cycle stability of the battery. It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples. Within the scope of the technical solution of the present application, embodiments having the same structure as the technical idea and exerting the same effect are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, various deformations that can be thought of by those skilled in the art are applied to the embodiments, and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, characterized in that: The invention comprises a positive electrode plate and an electrolyte. The positive electrode plate comprises a positive electrode film layer containing a slow-release polymer. The slow-release polymer can be dissolved in the electrolyte during the cycle of the secondary battery.
2. The secondary battery according to claim 1, characterized in that: At 20°C to 25°C, the absolute value of the difference between the solubility parameters of the sustained-release polymer and the electrolyte solvent is no more than 2J 1 / 2 / cm 3 / 2 .
3. The secondary battery according to claim 1 or 2, characterized in that: The weight average molecular weight of the sustained-release polymer is 25,000-200,000, and can be optionally 60,000-150,000.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: Based on the total mass of the positive electrode film layer, the mass percentage of the slow-release polymer is not higher than 4%, and can be optionally 0.5%-2%.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The sustained-release polymer includes at least one of an ester polymer, an ether polymer, a polymer containing a cyano group or a polymer containing a benzene ring.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The sustained-release polymer includes at least one of polymethyl methacrylate, a block copolymer of polymethyl methacrylate-propylene sulfite, polyethylene oxide, polyacrylonitrile or polystyrene.
7. The secondary battery according to any one of claims 1 to 4, characterized in that: The sustained-release polymer includes an ester polymer, and the electrolyte includes an ester solvent.
8. The secondary battery according to any one of claims 1 to 4, characterized in that: The sustained-release polymer includes an ether polymer, and the electrolyte includes an ether solvent.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The positive electrode film layer also includes a binder, and the mass ratio of the slow-release polymer to the binder is 1:2.5-1:0.5, and can be optionally 1:2-1:0.
8.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The viscosity of the electrolyte is 0.75 mPa·s-1.50 mPa·s, and can be optionally 0.96 mPa·s-1.15 mPa·s.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The secondary battery includes at least one of a lithium secondary battery, a sodium secondary battery, a magnesium secondary battery, and a potassium secondary battery.
12. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 11.
